The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/rda.12828
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different fragment sizes and cryoprotectants for cryopreservation of feline testicular tissues

Abstract: ContentsThis study aimed to evaluate tissue damage of feline testicles sectioned in two differ- (no alteration). When present, alterations were slight and the morphology was considered to be good (most classified in scores 1). Pyknosis was the main anomaly observed as score 2 in 54.6% and 58.4% of 0.3-cm 3 fragments cryopreserved in propanediol and glycerol, respectively (16.7% scored 2 in fresh tissue). In TBARS evaluation, 0.5-cm 3 fragments cryopreserved in glycerol produced less free radical compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…9 Testes contain a large number of germ cells, especially spermatogonia that can provide an unlimited source of male gametes if appropriately preserved and cultured. 10 In domestic species and also in some wild mammals, several studies have shown collection and preservation of testes from sexually immature individuals 11,12 and adult animals, 13 alive 14 or postmortem. 15 In general, a first strategy consists of conserving testicular tissue fragments appropriately using cryopreservation systems, such as slow freezing, fast freezing, and vitrification.…”
Section: Introductionmentioning
confidence: 99%
“…9 Testes contain a large number of germ cells, especially spermatogonia that can provide an unlimited source of male gametes if appropriately preserved and cultured. 10 In domestic species and also in some wild mammals, several studies have shown collection and preservation of testes from sexually immature individuals 11,12 and adult animals, 13 alive 14 or postmortem. 15 In general, a first strategy consists of conserving testicular tissue fragments appropriately using cryopreservation systems, such as slow freezing, fast freezing, and vitrification.…”
Section: Introductionmentioning
confidence: 99%
“…Fragments with 0.5 cm 3 of volume were compared to 0.3 cm 3 fragments. Larger fragments (0.5 cm 3 ) had less harmful effects on germ cells than smaller ones (0.3 cm 3 ) [ 23 ].…”
Section: Feline Speciesmentioning
confidence: 99%
“…The use of different cryoprotectants such as glycerol and propanediol has been proposed in the rapid freezing of cat testis. However, the histomorphological characteristics are better-preserved using glycerol [ 23 ].…”
Section: Feline Speciesmentioning
confidence: 99%